Majlis of the 'Others' : A reader for writers in the Gulf - Lewis, Dennis; Alaanoud Abusalim; Dennis Lewis; Laila Dahan; Neena Gandhi; Terri Lee Storseth (Pearson Custom Publishing; AUS American University of Sharjah, 2010)
Compiled by Dennis Lewis, Terri Lee Storseth, Laila Dahan, Alaanoud Abusalim and Neena Gandhi. Produced by Department of Writing Studies, American University of Sharjah. "The Majlis of the 'Others" presents a diverse range of readings that are culturally and thematically relevant to the life experiences and interests of contemporary writing students, of various nationalities, based in the Gulf. The book's readings are frequently challenging and provocative, and cover a variety of genres and perspectives.
English
Keywords: GN1-890 AnthropologyGCC